Clinical and epidemiological characteristics of probable cases of congenital Zika syndrome and dengue antibody levels, Tuxtla Gutierrez, Chiapas, Mexico. - Cardenas, Victor Manuel (2022)
A case series of suspected cases of congenital Zika syndrome in a maternity hospital in Tuxtla Gutierrez, Chiapas, Mexico was assembled to assess why they were not reported and explore the hypothesis of dengue antibody dependent Zika disease.  Clinical and imaging records, and interviews of a total of 13 of the cases revealed that only one of them was laboratory confirmed because appropriate specimens were not collected from the newborns as required by the case definition. 1) Microcephaly, 2) hypoplasia/hypogeneses, thinning or absence of brain structures, 3) multiple birth defects, 4) calcifications, and cysts, 5) meningocele/encephalocele and 6) hydrocephalus were found in 100%, 76.9%, 38.5%, 38.5%, 30.8%, and 23.1%, respectively. They clustered geographically, and 77% occurred within May 2016 to March 2017, and recalled or were told by a doctor they Zika fever. Using as referent a group of mothers who delivered normal newborns in the same hospital, and an 80% plaque reduction neutralization test for dengue virus 1 and 2, there was a four-fold increased risk of congenital Zika syndrome among those with dengue 1 antibody as compared to those with dengue 2 antibody (odds ratio = 3.6; 95% confidence interval: 0.7, 20.5), reaching only borderline statistical significance.  The case definitions of congenital Zika syndrome used during the pandemic probably needed to be simpler to gain sensitivity.